1995
DOI: 10.1029/95gl02668
|View full text |Cite
|
Sign up to set email alerts
|

Height gradient of F region vertical drift in the evening equatorial ionosphere

Abstract: Simultaneous measurements of F‐region vertical drift are made in the evening hours (1700–2100 IST) at Trivandrum (dip 0.6°N) and Kodaikanal (dip 4°N) on fifteen days during December 1993–January 1994 using the HF phase path technique on two different probing frequencies. The data are used to study the height dependence of vertical plasma drift in the bottomside F‐region in the dusk sector after correcting the drifts (at Kodaikanal) for meridional wind effects and chemical loss. It is found that growth and deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Some notable instruments such as Jicamarca incoherent scatter radar and Jicamarca Unattended Long‐term Ionosphere and Atmosphere radar are often used to obtain equatorial zonal electric fields [e.g., Fejer et al ., ; Kudeki and Fawcett , ; Hysell and Burcham , ]. HF Doppler radars have also been used widely over Indian region to study the density irregularities and the drift motion of the ionosphere [e.g., Viswanathan et al ., ; Balan et al , ; Subbarao and Krishnamurthy , ; Sastri et al ., ; Prabhakaran Nayar and Sreehar , ; Reddi et al ., ]. These observations have proved that ionospheric drifts or electric fields are crucial to understand the electrodynamics of the ionospheric plasma irregularities and related variabilities in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some notable instruments such as Jicamarca incoherent scatter radar and Jicamarca Unattended Long‐term Ionosphere and Atmosphere radar are often used to obtain equatorial zonal electric fields [e.g., Fejer et al ., ; Kudeki and Fawcett , ; Hysell and Burcham , ]. HF Doppler radars have also been used widely over Indian region to study the density irregularities and the drift motion of the ionosphere [e.g., Viswanathan et al ., ; Balan et al , ; Subbarao and Krishnamurthy , ; Sastri et al ., ; Prabhakaran Nayar and Sreehar , ; Reddi et al ., ]. These observations have proved that ionospheric drifts or electric fields are crucial to understand the electrodynamics of the ionospheric plasma irregularities and related variabilities in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations are being made by using both zonal and vertical drifts obtained from such ionosonde systems over Brazilian sector [ Abdu et al ., , ; Reinisch et al , ]. Over Indian region, HF Doppler radar is being widely used to study the height variation of these drifts [e.g., Sastri et al ., ; Prabhakaran Nayar and Sreehari , ]. The plasma vortex in the F region ionosphere during dusk sector, which is believed to be responsible for the generation of spread F onset, has been investigated using vertical and zonal drift motions of the HF Doppler radar over Trivandrum [ Sreehari et al ., ; Mathew and Nayar , ].…”
Section: Introductionmentioning
confidence: 99%
“…Ionosonde measurements have been made in the Peruvian, Brazilian, and Indian sectors [e.g., Abdu et al , 1981; Sastri et al , 1995]. Plasma drift observations using various techniques have also been reported from equatorial and low‐latitude stations, although they are not as extensive as those reported for Jicamarca [e.g., Abdu et al , 1985; Batista et al , 1986; Batista et al , 1996; Jahn et al , 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Now, according to Sastri et al (1995), the drift velocity data measured at Trivandrum has shown a negative gradient of with height during the daytime up to late evening. This also corroborates to the works of Balan and Bailey (1996).…”
Section: Approachmentioning
confidence: 98%